Case report: A patient with brachio-cervical inflammatory myopathy was misdiagnosed as flail arm syndrome - Sun, Hui; Wei, Xiao-Jing; Han, Ye; Wang, Yong-Chun; Wang, Zi-Yi; Yu, Xue-Fan (Frontiers in Immunology, 2024)
Brachio-cervical inflammatory myopathy (BCIM) is a rare inflammatory myopathy characterized by dysphagia, bilateral upper limb atrophy, limb-girdle muscle weakness, and myositis-specific antibody (MSA) negativity. BCIM has a low incidence and is commonly associated with autoimmune diseases. We present a case report of a 55-yearold man with progressive upper limb weakness and atrophy, diagnosed with flail arm syndrome (FAS). The initial electromyography revealed extensive spontaneous muscle activity and increased duration of motor unit potentials (MUPs). During follow-up, evidence of myogenic damage was observed, as indicated by a decreased duration of MUPs in the right biceps muscle. Laboratory and genetic testing ruled out hereditary or acquired diseases. Negative serological antibodies for myasthenia gravis. Hereditary or acquired diseases were ruled out through laboratory and genetic testing. Whole-body muscle magnetic resonance imaging (MRI) showed extensive edema and fat replacement in the bilateral upper limbs, scapular, and central axis muscles, while the lower extremities were relatively mildly affected. Muscle biopsy revealed numerous foci of inflammatory cells distributed throughout the muscle bundle, with predominant CD20, CD138, and CD68 expression, accompanied by a light infiltration of CD3 and CD4 expression. The muscle weakness improved with the combination of oral prednisone (initially 60 mg/day, tapered) and methotrexate (5 mg/week) treatment.